Upaya Perwujudan Lingkungan Bersih Melalui Pengolahan Sampah Organik menjadi Pupuk Kompos - Nathasa Pramudita Irianti; Zuni Mitasari; Antonius Alam Wicaksono (Universitas Pahlawan Tuanku Tambusai, 2023)
This activity aims to overcome the problems faced by one of the Adiwiyata schools in Malang City, namely SMPN 26 Malang in managing organik waste to make it more useful, namely compost. Based on interviews conducted by the service team with the school, it was agreed that three methods would be carried out in this activity, namely (1) As a solution for organik waste management, the service team provided a solution by managing organik waste into compost, (2) Because the school did not have adequate understanding of waste management into compost, training is conducted on processing waste into compost and (3) because so far there has been no assistance regarding the practice of processing organik waste, the practice of managing organik waste into compost is carried out. All activities have been carried out well. All of the training and mentoring can be completed and the dry leaf waste that was previously scattered can be managed into organik waste which can then be used by school residents to fertilizer plants in the surrounding environment.